Analisis Pola Asuh Orang Tua Dalam Partisipasi Orang Tua Murid Untuk Meningkatkan Kemampuanmenghafal Alfabet Anak Usia 4-5 Tahun Di Tk Al-Ichsan - aweni, eka isti; virdaus, varia virdania (Universitas Narotama, 2024)
The aim of this research is to prepare pattern analysis Foster Parents in Parental Participation Students To Improve Ability Memorize Alphabet Age Children 4-5 Year In Kindergarten Al-Ichsan . The method used was a Qualitative Descriptive Analysis interview approach. The informants chosen were 4 (four) parents of Al-Ichsan Kindergarten students. The data collection techniques used were observation, interviews and documentation. This research uses a data validity test through source triangulation, then the data is analyzed and conclusions are drawn. The results of research using participation theory, parenting style theory, and early childhood education theory show the results of several factors that influence children's letter learning at Al-Ichsan Kindergarten. Participation, authoritarian parenting, democratic parenting, sensitive learning periods, role play and creative activities, as well as respect for culture and social context are the main focus. The results of the research show that parents' active and creative participation supports children's learning, authoritarian parenting is used by informant number 2. Democratic parenting is used by informants number 1, 3 and 4, then no one uses this pattern of primitive parenting. The weakness of this research is the primitive parenting style where there are no parent informants who use this method in learning the alphabet to children.